2020
DOI: 10.1038/s41586-020-2940-2
|View full text |Cite|
|
Sign up to set email alerts
|

A network of transcriptional repressors modulates auxin responses

Abstract: Alongside spatio-temporal distribution of developmental signals themselves, the regulation of signalling capacity plays a pivotal role in setting developmental responses in both plants and animals (1). The hormone auxin is a key signal for plant growth and development that acts through the AUXIN RESPONSE FACTOR (ARF) transcription factors (2-4). Subsets of ARFs, the conserved Class A ARFs (abbreviated ARF ClassA ) (5), are transcriptional activators of auxin-responsive target genes, and are essential for regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 57 publications
2
33
0
Order By: Relevance
“…Interestingly, MP and ARF10 are not expressed homogenously in the RAM (Rademacher et al, 2011), suggesting that the cellular context could be important to define the effect of auxin over WOX5 (García-Gómez et al, 2017). Particularly, MP is expressed in the QC cells but not ARF10 (Rademacher et al, 2011;Truskina et al, 2020), which raises the hypothesis that particular ARF profiles could be important for the auxin regulation of WOX5 expression in these cells. Hence, it is of interest to uncover the mechanisms behind the expression patterns of these ARFs in the RAM in order to understand the specificity of auxin responses in the root meristem; however, there is still no evidence about it.…”
Section: Figure 1 | (A)mentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, MP and ARF10 are not expressed homogenously in the RAM (Rademacher et al, 2011), suggesting that the cellular context could be important to define the effect of auxin over WOX5 (García-Gómez et al, 2017). Particularly, MP is expressed in the QC cells but not ARF10 (Rademacher et al, 2011;Truskina et al, 2020), which raises the hypothesis that particular ARF profiles could be important for the auxin regulation of WOX5 expression in these cells. Hence, it is of interest to uncover the mechanisms behind the expression patterns of these ARFs in the RAM in order to understand the specificity of auxin responses in the root meristem; however, there is still no evidence about it.…”
Section: Figure 1 | (A)mentioning
confidence: 96%
“…The proposed links between patterning mechanisms and hormonal signaling pathways may be critical for understanding how cells will respond to auxin and may constitute a generic mechanism for the spatial specificity of hormonal responses in plant development. Interestingly, it has been shown that the chromatin of several ARFs is constitutively open for transcription, and a series of transcriptional repressors affect their expression (Truskina et al, 2020). Under such a scenario, SHR-JKD and SHR-MGP could act as the repressors that are behind the expression patterns of ARF10 and MP, respectively, and that underlie the spatial specificity of their activity in the RAM.…”
Section: Figure 1 | (A)mentioning
confidence: 99%
“…Particularly, GRN inferred from yeast one- and two-hybrid approaches have greatly contributed to our understanding of development and stress in Arabidopsis. These GRN have provided new insights into secondary cell wall gene regulation under abiotic stress ( Taylor-Teeples et al, 2014 ), showed coordinated transcriptional regulation of enzymes involved in nitrogen metabolism ( Gaudinier et al, 2018 ) and identified upstream regulation of AUXIN RESPONSE FACTORS to modulate auxin signaling throughout development ( Truskina et al, 2020 ).…”
Section: Single-cell Omics Approachesmentioning
confidence: 99%
“…Another challenge is that both enhancers and silencers often respond to the same TFs (Alexandre and Vincent, 2003;Iype et al, 2004;Liu et al, 2014;Martínez-Montañés et al, 2013;Peng et al, 2005;Stampfel et al, 2015;White et al, 2016). Many TF-bound sequences act as silencers (Clyde et al, 2003;Doni Jayavelu et al, 2020;Gisselbrecht et al, 2020;Grossman et al, 2017;Kwasnieski et al, 2014;Truskina et al, 2020;White et al, 2013), but predictions of cis-regulatory sequences based on TF binding or chromatin state often do not make a distinction between these two classes of sequence. Since enhancers in one cell type are often silencers in other cell types (Barolo and Posakony, 2002;Clyde et al, 2003;Gisselbrecht et al, 2020;Junion et al, 2012;Parker et al, 2011;Rachmin et al, 2015;Swanson et al, 2010), enhancers and silencers likely share similar sequence features.…”
Section: Introductionmentioning
confidence: 99%